2011
DOI: 10.1200/jco.2010.31.4427
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Guided Tamoxifen Dosing Increases Active Metabolite Exposure in Women With Reduced CYP2D6 Metabolism: A Multicenter Study

Abstract: This study demonstrates the feasibility of genotype-driven tamoxifen dosing and demonstrates that doubling the tamoxifen dose can increase endoxifen concentrations in IM and PM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
118
4
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 43 publications
11
118
4
9
Order By: Relevance
“…It could be additionally demonstrated that a daily dose adjustment from 20 to 40 mg could sufficiently increase the endoxifen concentration in patients with impaired CYP2D6 function. Although this data indirectly support the main hypothesis, there is no strong evidence about the influence of endoxifen levels on the clinical course of breast cancer [30] .…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…It could be additionally demonstrated that a daily dose adjustment from 20 to 40 mg could sufficiently increase the endoxifen concentration in patients with impaired CYP2D6 function. Although this data indirectly support the main hypothesis, there is no strong evidence about the influence of endoxifen levels on the clinical course of breast cancer [30] .…”
Section: Discussioncontrasting
confidence: 71%
“…A recent work of Zafra-Ceres et al [29] studied 90 Spanish women with ER positive breast cancer concluded that the CYP2D6*4/*4 genotype was associated with statistically significant lower 4-OH tamoxifen and endoxifen levels. Irvin et al [30] examined a brighter combination of CYP2D6 alleles and reported similar results. It could be additionally demonstrated that a daily dose adjustment from 20 to 40 mg could sufficiently increase the endoxifen concentration in patients with impaired CYP2D6 function.…”
Section: Discussionmentioning
confidence: 70%
“…Blant kaukasere mangler 5 -10 % CYP2D6-funksjon som følge av homozygot nedarving av inaktiverende variantalleler i dette genet. Videre er naermere 40 % heterozygote baerere av genvarianter som medfører nedsatt CYP2D6-funksjon (4,5).…”
Section: Genetisk Variasjonunclassified
“…15,[20][21][22] Thus, legitimate concerns have been raised over concurrent use of TAM with drugs that inhibit this enzyme or in patients with inherited CYP2D6 deficiency. Like TAM, TOR is readily N-demethylated to produce its major circulating metabolite NDM TOR.…”
mentioning
confidence: 99%
“…19 CYP2D6 is a clinically relevant enzyme for TAM as decreased activity by allelic variation or competitive inhibition (e.g., selective serotonin reuptake inhibitor (SSRI) antidepressants) results in lower conversion of TAM to its active metabolites. 15,[20][21][22] Thus, legitimate concerns have been raised over concurrent use of TAM with drugs that inhibit this enzyme or in patients with inherited CYP2D6 deficiency. Like TAM, TOR is readily N-demethylated to produce its major circulating metabolite NDM TOR.…”
mentioning
confidence: 99%